A Practical 3D-Printed Model for Training of Endoscopic and Exoscopic Intracerebral Hematoma Surgery with a Tubular Retractor - Zhu, Junhao; Wen, Guodao; Tang, Chao; Zhong, Chunyu; Yang, Jin; Ma, Chiyuan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objective To present a three-dimensional (3D)-printed model that simulates endoscopic and exoscopic intracerebral hematoma (ICH) surgery with a tubular retractor.Methods We used 3D printing technology to develop the model that consisted of the skull frame and a replaceable inserted module. Edible gelatin and animal blood were placed into the module to mimic brain tissue and the hematoma. Twenty neurosurgeons were recruited to participate in our training program that required the use of an endoscope and an exoscope to aspirate the hematoma with a tubular retractor. Five postgraduates were asked to complete the entire training with the endoscope five times. Questionnaires were distributed for feedback after the training program.Results The more experienced surgeons obviously performed better than the rather inexperienced surgeons, verifying that our model could reflect the ability of the trainees. As the training progressed, the scores of the postgraduates increased, and the average score of the fifth training was obviously higher than the first score. No significant differences were observed in the trainees' performance with the endoscope and the exoscope. The feedback questionnaires showed the average score for value of the simulator as a training tool was a 3.65 (on a 4-point scale). Our model received better comments regarding the bone texture (mean: 3.20), the brain tissue texture (mean: 3.20), and the experience in aspirating the hematoma (mean: 3.10). The surgical position (mean: 2.95), surgical approach (mean: 2.90), and simulated brain tissue (mean: 2.85) should be improved.Conclusion Our model was practical for endoscopic and exoscopic ICH surgery training. The results of our program showed that prior surgical experience benefited the mastery of both the endoscopic and the exoscopic ICH surgery in the 3D-printed model. Our model could make mastering basic skills more efficient.
Keywords: endoscope; 3D-printed model; intracerebral hematoma; evacuation surgery; tubular retractor